Trends and risk factors for severe perineal trauma during childbirth in New South Wales between 2000 and 2008: a population-based data study. Issue 5 (17th May 2013) - Dahlen, Hannah; Priddis, Holly; Schmied, Virginia; Sneddon, Anne; Kettle, Christine; Brown, Chris; Thornton, Charlene
Abstract : Objectives: To determine trends and risk factors for severe perineal trauma between 2000 and 2008. Design: This was a population-based data study. Setting: New South Wales, Australia. Participants: 510 006 women giving birth to a singleton baby during the period 2000–2008. Main outcome measures: Rates of severe perineal trauma between 2000 and 2008 and associated demographic, fetal, antenatal, labour and delivery events and factors. Results: There was an increase in the overall rate of severe perineal trauma from 2000 to 2008 from 1.4% to 1.9% (36% increase). Compared with women who were intact or had minor perineal trauma (first-degree tear, vaginal graze/tear), women who were primiparous (adjusted OR (AOR) 1.8 CI (1.65 to 1.95), were born in China or Vietnam (AOR 1.1 CI (1.09 to 1.23), gave birth in a private hospital (AOR 1.1 CI (1.03 to 1.20), had an instrumental birth (AOR 1.8 CI (1.65 to 1.95) and male baby (AOR 1.3 CI (1.27 to 1.34) all had a significantly higher risk of severe perineal trauma. Only giving birth to a male baby, adjusted for birth weight (AOR 1.5 CI (1.44 to 1.58), remained significant, when women with severe perineal trauma were compared with all other women not experiencing severe perineal trauma. This association increased over the study period. Conclusions: To our knowledge, this is the first time that having a male baby has been found to exert such a strong independent risk for severe perineal trauma and the increasing significance of this in recent years needs further exploration.